2018
DOI: 10.1021/acsmedchemlett.7b00503
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibitors of Hepatitis C Virus NS3 Protease: Employment of a Difluoromethyl Group as a Hydrogen-Bond Donor

Abstract: The design and synthesis of potent, tripeptidic acylsulfonamide inhibitors of HCV NS3 protease that contain a difluoromethyl cyclopropyl amino acid at P1 are described. A cocrystal structure of with a NS3/4A protease complex suggests the presence of a H-bond between the polarized C-H of the CHF moiety and the backbone carbonyl of Leu135 of the enzyme. Structure-activity relationship studies indicate that this H-bond enhances enzyme inhibitory potency by 13- and 17-fold compared to the CH and CF analogues, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…[19] Other bioactive molecule containing the difluoromethyl group are highlighted in Figure 3. [20,21] In summary,t he uniquep hysicochemical properties of a CHF 2 group-high metabolic stability compared with the methyl group, lower lipophilicity compared with the CF 3 group, and hydrogen-bond ability-make it an important substituent for drug discovery and agrochemistry.…”
Section: Trifluoromethyl (Cf 3 )Versus Difluoromethyl (Chf 2 )mentioning
confidence: 99%
“…[19] Other bioactive molecule containing the difluoromethyl group are highlighted in Figure 3. [20,21] In summary,t he uniquep hysicochemical properties of a CHF 2 group-high metabolic stability compared with the methyl group, lower lipophilicity compared with the CF 3 group, and hydrogen-bond ability-make it an important substituent for drug discovery and agrochemistry.…”
Section: Trifluoromethyl (Cf 3 )Versus Difluoromethyl (Chf 2 )mentioning
confidence: 99%
“…17 Indeed, several examples displaying the involvement of H-bond interactions by this group at the active sites of receptors were reported. [18][19][20][21] Recently, this issue was investigated by us 22,23 by determining the solute H-bond acidity (A, the ability of a molecule to act as a H-bond donor) of various difluoromethylated compounds. The results revealed that the CF 2 H group acts as a relatively weak H-bond donor, with A values that strongly depend on the attached functional group (i.e., FGCF 2 H, A = 0.035-0.165) (Figure 1, A).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to monouoro-and triuoromethyl groups, the diuoromethyl function (-CF 2 H) is another uorinated alkyl moiety of great interest since it plays critical roles as a lipophilic isostere of hydroxyl group as well as a hydrogen bond donor. [37][38][39] However, synthesis of such molecules is not straightforward as in case of mono-and triuorinated analogues. 40 Therefore, studies on their properties and possible applications seem to be still an unexplored eld, worth to investigate.…”
Section: Introductionmentioning
confidence: 99%